2022
DOI: 10.1038/s43856-022-00164-x
|View full text |Cite
|
Sign up to set email alerts
|

Dental biorhythm is associated with adolescent weight gain

Abstract: Background Evidence of a long-period biological rhythm present in mammalian hard tissue relates to species average body mass. Studies have just begun to investigate the role of this biorhythm in human physiology. Methods The biorhythm is calculated from naturally exfoliated primary molars for 61 adolescents. We determine if the timing relates to longitudinal measures of their weight, height, lower leg length and body mass collected over 14 months b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Accumulating evidence indicates that RP reflects an underlying biological cycle that acts upon the mammalian hypothalamus. It is hypothesized that the cycle regulates cell growth when compared between mammalian species (Bromage et al, 2009), and it has been observed that RP relates to body mass and maturation rate within human adolescents (Mahoney et al, 2022). These findings have been important for developing ideas about the evolution and pace of primate life history (Bromage et al, 2012), whereby the higher mean RP of recent humans relative to other hominins may relate to a unique life history profile (e.g., Hogg et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that RP reflects an underlying biological cycle that acts upon the mammalian hypothalamus. It is hypothesized that the cycle regulates cell growth when compared between mammalian species (Bromage et al, 2009), and it has been observed that RP relates to body mass and maturation rate within human adolescents (Mahoney et al, 2022). These findings have been important for developing ideas about the evolution and pace of primate life history (Bromage et al, 2012), whereby the higher mean RP of recent humans relative to other hominins may relate to a unique life history profile (e.g., Hogg et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Teeth were sectioned through the midline of the canines and the distal cusps of the molar passing through the dentin horn. Standard procedures (see Mahoney et al, 2022) were employed but with one modification to accommodate subsequent chemical and molecular analyses. Specifically, teeth were embedded in crystal bond (Agar Scientific) before additional embedding in resin (Buehler EpoxiCure), so that the sectioned portions of each tooth could be removed from the resin.…”
Section: Histologymentioning
confidence: 99%
“…We do not offer an hypothesis but suggest that a tentative set of empirically supported relationships may offer clues for future investigations. First, biorhythm variation identified in deciduous teeth (the number of daily cross‐striations between striae of Retzius) from a sub‐sample of these Dunedin school children is associated with their weight gain over the full period of the study, but not in a linear manner (Mahoney et al 2022). A portion of the variation in this expressed biorhythm might reflect physiology that is more sensitive to changing conditions of energy availability.…”
Section: Discussionmentioning
confidence: 99%
“…Students were recruited in their last year of primary school and followed as they transferred to intermediate schools in the Dunedin area. The participants were part of the Biorhythm of Childhood Growth project (Mahoney et al 2022). The project is an ongoing prospective cohort study that investigates childhood development in middle‐income children from Southern New Zealand.…”
Section: Participants and Methodsmentioning
confidence: 99%